Empty Homes and Acquisitive Crime: Does Vacancy Type Matter? - Roth, Jeffrey J. (American journal of criminal justice, 2019)
Research suggests that vacant homes are associated with a variety of negative outcomes for communities, including higher rates of some crimes. A few studies in this vein have examined the effects of particular types of vacancy, such as abandoned homes, empty occupiable residences, seasonal housing, and undeveloped lots. However, these works have focused on a single state or urban area. The present study sought to advance the understanding of vacancy’s relationship to acquisitive crime (burglary, robbery, and larceny) by including several vacancy rates (homeowner, rental, seasonal, and overall) as distinct predictors and by using a sample of large cities from across the United States. The analysis also controlled for social, demographic, and economic factors relevant to crime and vacancy. Results from negative binomial regression models indicated that the relationship between empty residences and crime varied depending upon the particular form of vacancy and upon the type of criminal offense.